Recent trends in philosophical logic - Wansing, Heinrich; Willkommen, Caroline; Ciuni, Roberto (Trends in Logic, Studia Logica Library, 2014)
This volume presents recent advances in philosophical logic with chapters focusing on non-classical logics, including paraconsistent logics, substructural logics, modal logics of agency and other modal logics. The authors cover themes such as the knowability paradox, tableaux and sequent calculi, natural deduction, definite descriptions, identity, truth, dialetheism, and possible worlds semantics.   The developments presented here focus on challenging problems in the specification of fundamental philosophical notions, as well as presenting new techniques and tools, thereby contributing to the development of the field. Each chapter contains a bibliography, to assist the reader in making connections in the specific areas covered. Thus this work provides both a starting point for further investigations into philosophical logic and an update on advances, techniques and applications in a dynamic field.   The chapters originate from papers presented during the Trends in Logic XI conference at the Ruhr University Bochum, June 2012.